Prescribing Pattern of Benzodiazepine Receptor Agonists (BZRA) and Factors Associated With Duration of BZRA Use in a Malaysian Psychiatry Outpatient Clinic - Yong, Shire Li; Tan, Huey Jing Renee; Chemi, Norliza; Syed Mokhtar, Sharifah Suziah; Neo, Yee Wen; Mohd Zamri, Nor Maliza; Sahidan, Elina; Tee, Sue Kee (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Benzodiazepine receptor agonist (BZRA) are among the most frequently used psychotropic medications worldwide. We aim to understand the pattern of prescription of BZRA in the government healthcare facilities and identify factors affecting the likelihood of BZRA prescription and duration of use. Method: This is a retrospective study. Data was obtained from record of outpatient clinical notes. Medications studied were midazolam, alprazolam, lorazepam, bromazepam, clonazepam, diazepam and zolpidem. Mean duration per prescription, mean dosage perprescription and duration per patient per year were calculated for each sedative hypnotic. The likelihood of factors affecting duration of prescription were also analysed. Results: The prevalence of sedative hypnotic use in psychiatry outpatient clinic was 12.16%. Clonazepam was found to have the longest duration per patient per year (306.5 days). Insomnia and anxiety are the two most common reasons for sedative hypnotic prescription. Factors found to affect duration of prescription were unemployment, borderline personality disorder, alcohol and substance use disorders. Conclusion: Implementation of effective monitoring system on sedative hypnotic prescribing and increase use of non-pharmacological interventions for insomnia and anxiety are necessary to curb prolonged use of sedative hypnotic.